#TITLE_ALTERNATIVE# - Rahman (NIM 122 03 011), Fadli
Abstract: In the petroleum industry, reserves estimation is an aspect that has to be done periodically with considering many factors that affect the process. During the producing time, remaining reserves estimation became a vital phase of reservoir engineering task. One of the methods that very popular is the analysis of production performance graphs. This method, also applied to forecast the future production performance, is usually used because of the effectiveness, short time and low cost of analysis and estimation process. So far, various plots were made for production performance analysis purposes. One of the graphs is semi-log plot of rate vs. time, or well-known as decline curve. Other plot that also popular is semi-log plot of water-oil ratio vs. cumulative oil production. The graphs can applied for determining remaining reserves and forecasting the future production performance with assumptions used to substance the estimation result. Estimation results using OFM (OilField Manager) software show the significance difference between both methods. Analysis method of rate-time yields estimated reserves 28.87 MMSTB, while WOR-cumulative production yields 44.85 MMSTB. Results show the distinguish of character between rate-time and WOR-cumulative production plot.